Using locally available fertilisers to enhance the yields of swidden farmers in Papua New Guinea - Hazenbosch, M; Sui, S; Isua, B; Beauchamp, E; Frouz, J; Imale, K; Jimbude, M; Milner-Gulland, EJ; Novotný, V; Veselá, H; Morris, RJ (Elsevier, 2021)
Context Swidden agriculture (a type of small-scale agriculture) is crucial to the livelihood and food security of millions of people in tropical regions. Social-ecological changes, including population growth and anti-swidden policies, are putting pressure on the existing swidden system to increase agricultural productivity in a sustainable way. Enhancing soil fertility is a promising option for increasing crop yields and extending lifetimes of agricultural fields, thereby reducing the demand to clear new land. However, there is limited information on how swidden farmers can best maintain soil fertility.